1996
DOI: 10.1159/000147794
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Development in the Ventral Prostate, Anterior Prostate and Seminal Vesicle of the Rat

Abstract: The prostate and seminal vesicle (SV) are androgen-dependent secretory glands of the male genital tract. They produce the bulk of the seminal secretions. The object of the present study was to examine and document the ontogeny of stromal maturation in the rat anterior and ventral prostate and SV. These organs have a loosely organized cellular mesenchyme during fetal development. During prostatic development the mesenchyme condensed to form smooth muscle sheaths immediately surrounding the epithelium, with loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
3
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 4 publications
6
76
3
4
Order By: Relevance
“…It is important to realize that the major structural modification during the first postnatal week is canalization, as stereology showed no significant changes in the volumes of epithelium and stroma, which appears to take place later on (Donjacour and Cunha, 1988;Hayward et al, 1996b;Vilamaior et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to realize that the major structural modification during the first postnatal week is canalization, as stereology showed no significant changes in the volumes of epithelium and stroma, which appears to take place later on (Donjacour and Cunha, 1988;Hayward et al, 1996b;Vilamaior et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During development, the mesenchyme condenses around the ducts in a proximal to distal fashion to encase the ducts with smooth muscle actin (SMA), the earliest smooth muscle marker expressed, and desmin, a later marker (33). To determine the state of smooth muscle differentiation, we examined the expression of SMA and desmin at P5, which corresponds to the initiation of secondary branching in the anterior prostate.…”
Section: Characterization Of Gene Expression In Abnormal Prostatementioning
confidence: 99%
“…On the other hand, it is also possible that the continuous layer of smooth muscle formed around the main ducts as a result of the absence of branching. To further understand this branching defect, we examined expression of androgen receptor by immunofluorescent staining, because several investigators had demonstrated that postnatal prostate branching morphogenesis and differentiation of the stroma are highly regulated by androgen (32,33,35). Androgen receptor was expressed continuously around the primary and secondary ducts of Klf6 f/f Nkx3.1 Ï©/Ï© (supplemental Fig.…”
Section: Characterization Of Gene Expression In Abnormal Prostatementioning
confidence: 99%
“…3). For example, cells of the embryonic UGM form a layer of smooth muscle, which lines the epithelium and exhibits contractile activity to aid expulsion of prostatic fluid into the ejaculate (Hayward et al, 1996b). The adult prostate stroma also contains a large population of mature fibroblasts that secrete extracellular matrix, consisting of fibrillar proteins, glycoproteins and proteoglycans that form a structural network and mediate growth factor signaling (Tuxhorn et al, 2001).…”
Section: Introductionmentioning
confidence: 99%